A Study of Phenology and Nursery Behaviour of Andaman Timber Species - Ganapathy, P. M.; Rangarajan, M. (Indian Forester, 1964)
A general account of the Andaman Forests, their compositional characteristics and response in physiological behaviour to climatic factors are given as prologue to the study of phenology and behaviour in nursery of the important timber species of the Islands. Existing knowledge of phenology of these important species and their response to artificial propagation is either scanty, diffuse or totally unavailable. This study is a summation of available information on the subject supplemented to a large extent by original observations in ptots laid out to statistical conformity. The information contained is hoped to be useful to those especially of mainland forest departments who are keen to introduce Andaman species in their respective zones. To foresters of these islands the data presented are of little value as most of the species respond more favourably to carefully phased natural regeneration operations.